UNGKAPAN PENGHALUS DALAM BAHASA INGGRIS DAN BAHASA TABARU (SUATU ANALISIS KONTRASTIF) - MALEMPI, FIFIEN; JANSEN, FRIEDA TH.; PAMANTUNG, RINA P. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTThis study entitled â€œEuphemism in English and Tabaru Language: A Contrastive Analysisâ€ is an can effort to identify, classify, describe and to contrast euphemism words or phrases that are used to substitute taboo words in English and Tabaru Language. The English data have been collected from English previous researches done by student of Faculty of Humanities, internet articles, and some books whereas the Tabaru Language data have been collected by giving interview to some informants, who are native speakers of Tabaru. After identifying, classifying and describing the data from both languages then they are contrasted by using concept of Lado about contrastive analysis. The main of contrastive analysis is for finding the differences from both of languages. The writer will be used Wardaugh (1986) and Fromkin (1997) theory to analyze the data from English and Tabaru language. The findings show that the differences of the types of Euphemism in both languages these are: English has no euphemism words or phrases to substitute taboo words related to kinship terms, Euphemism word or phrase related to crime, euphemism words or phrase related to job unemployment, and exile, Euphemism related to superstition while the Tabaru has these four things. The study is expected to help students in learning and identifying Euphemism in their own regional language._________________________Keywords: Euphemism, English and Tabaru Language, Contrastive Analysis.